The partition of Palestine - Watson, Charles R. (United Presbyterian Board of Christian Education, 1948)
Ignorance and indifference of Americans criticized -- Americans mistaken in thinking all Jews Zionists -- Zionist movement repudiated by many Jews -- Partition supporters overlook Atlantic charter -- Injustice to Arab population unworthily ignored -- Is partition fulfilment of prophecy? -- Is partition a practical solution? -- Americans should not become entangled in problem.